Evaluation of Computer-Based Testing Website Quality Using the DeLone and McLean Information System Success Model - Muhamad Sakinul Wadi; Sofiansyah Fadli; Mohammad Taufan Asri Zaen (Universitas Trilogi, 2026)
The rapid development of information technology has significantly impacted the education sector, particularly in the implementation of computer-based examination systems. This study aims to analyze and evaluate the quality of a Computer-Based Testing (CBT) website at SMK Bangun Bangsa using the DeLone and McLean Information System Success Model. A quantitative approach was employed by collecting primary data through questionnaires distributed to 260 students from grades X and XI of SMK Bangun Bangsa who had experience using the CBT system. The respondents represented various demographic backgrounds in terms of gender, age, and academic majors. The variables analyzed include system quality, information quality, service quality, user satisfaction, and net benefits. Data analysis was conducted using descriptive statistical methods, supported by validity and reliability testing to ensure the accuracy and consistency of the research instrument. The results indicate that the CBT system has generally performed well. System quality obtained a score of 75.4% (good category), indicating that the system is easy to use despite minor technical issues. Information quality achieved 77.7% (very good), reflecting that the system provides accurate, relevant, and understandable information. Service quality recorded the lowest score of 72.2% (good), suggesting the need for improvement in security and technical support. Meanwhile, user satisfaction reached 81.6% and net benefits 80%, both categorized as very good, indicating that the system enhances efficiency and provides a positive user experience. This study contributes to evaluating the effectiveness of CBT systems in vocational education environments and highlights the importance of improving service quality and system reliability to achieve optimal system performance. Future research is recommended to expand the study scope and integrate additional models for deeper analysis.